The Real Economy and the Banking System in Bulgaria: Empirical Analysis 1991-2006 - Statev, Stati (Research Papers, 2009)
This research paper makes an empirical study of the independent development of the real economy and the banking system in Bulgaria in two time periods, divided by the date on which the currency board mechanism was implemented in the country. It also studies the existing relationships and interactions between the real economy and the banking system in terms of contents and temporal development. The study is based on the employment of a large number of indicators: 9 – for the real economy, and 32 – for the banking system, which reveal various aspects of the functioning of these two sectors. A conclusion has been made on the basis of descriptive analysis, that the dynamic developments of the real economy and the banking system respectively have their own particular behavior under two different monetary regimes. Over the period of the first such monetary regime, the depth and activity of banking intermediation, compared with the size of the economy, are relatively high but without any positive effect on the real economy because of the inefficiency and poor effectiveness of the real sector and the inadequacy of the banking system. Parallel changes in both the banking and real sectors are observed in 1996 and 1997, when the decline of banking as a whole, coupled with the shrinking of the commercial banks in particular, can be accepted both to be provoked and accompanied by the shrinking of aggregate output and to affect it at the same time. At the beginning of the second period, banks manifest rather a conservative behavior with respect to the national economy, which is substantiated by the shock experienced in result of the banking crisis, which prompts them to wait for more secure indications of sustainability in the development of the real sector. Since the beginning of the current century, what has been observed is an enhanced interaction between the banking and the real sectors, but no direct correspondences have been registered between the changes in the two sectors on a year-by year basis.